(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
Cupping therapy, a traditional alternative medicine practice, has garnered increasing interest as a holistic health approach. Despite its historical significance, there remains a lack of comprehensive awareness and understanding of its benefits within various communities. Previous studies have not adequately addressed the implementation and public perception of cupping therapy in local contexts, particularly among underserved populations. This study aims to evaluate the effectiveness of a cupping health program conducted by the Muhammadiyah Sidoarjo University KKN group in the Barengkrajan community, focusing on enhancing public awareness and accessibility to alternative health services. Through direct therapy sessions led by qualified professionals and educational initiatives, the program achieved high participant satisfaction rates and a notable increase in interest towards alternative therapies. This program uniquely combines practical cupping therapy with educational outreach, providing a model for similar community health interventions. The findings suggest that structured cupping programs can significantly improve community health perceptions and utilization of alternative therapies, warranting further exploration and development to integrate such practices into broader public health strategies. Highlights: • High participant satisfaction demonstrated the effectiveness of direct therapy sessions. • Educational initiatives significantly increased community interest in alternative therapies. • The program serves as a model for integrating traditional practices into modern health strategies. Keywords: cupping therapy, alternative medicine, public health, community awareness, health intervention